2006
DOI: 10.2119/2006-00065.valentine
|View full text |Cite
|
Sign up to set email alerts
|

Passive Immunization to Outer Membrane Proteins MLP and PAL Does Not Protect Mice from Sepsis

Abstract: Multiple older studies report that immunoglobulin directed to rough mutant bacteria, such as E. coli J5, provides broad protection against challenge with heterologous strains of Gram-negative bacteria. This protection was initially believed to occur through binding of immunoglobulin to bacterial lipopolysaccharide (LPS). However, hundreds of millions of dollars have been invested in attempting to develop clinically-effective anti-LPS monoclonal antibodies without success, and no study has shown that IgG from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The mouse burn wound infection model was performed as described previously [ 15 ], followed immediately by subcutaneous injection of E. coli O4 at log phase into the burned area as described. Blood was collected from the tail vein at different times, except the terminal bleed, which was done by cardiac puncture.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mouse burn wound infection model was performed as described previously [ 15 ], followed immediately by subcutaneous injection of E. coli O4 at log phase into the burned area as described. Blood was collected from the tail vein at different times, except the terminal bleed, which was done by cardiac puncture.…”
Section: Methodsmentioning
confidence: 99%
“…This model of sepsis due to peritonitis was adapted from Ahrenholz and Simmons as described previously [ 15 , 16 ]. Mice were implanted with a fibrin clot with or without E. coli O4 as desired or with 250 μl of blood in the peritoneum.…”
Section: Methodsmentioning
confidence: 99%
“…PAL and MLP were prepared from E. coli bacteria as described, and were confirmed to contain a single protein band by gold staining (29, 34). Pam3CysSKKK was purchased (EMC Microcollections, Tubingen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…The effect of passive immunization with mono‐ and polyclonal anti‐Pal antibodies has been tested in three different mouse models of sepsis (cecal ligation and puncture, an infected burn model, and an infected fibrin clot model mimicking peritonitis). However, these trials indicated that this type of strategy does not have any protective/therapeutic effect (Valentine et al , 2006).…”
Section: Role Of Pal In the Process Of Pathogenesismentioning
confidence: 99%